Organizational Culture in Healthcare Services: Characteristics, Advantages and Disadvantages - Agoritsa Koulouri (Ene, 2019)
Organizational culture - a system of rules, values and behaviors of an organization's - is a key factor of the functionality, performance and quality of the services it provides. Organizational culture is the personality of the organization. It is a structured set of key assumptions that have been invented, discovered or developed by a team of the organization in order to cope with problems of external adaptation or internal integration. Organizational culture creates a sense of identity for every health formation, while it is serving as a reference frame for decisions and actions. The purpose of this review is to present the conceptual framework of organizational culture in the light of its existence in health organizations. Additionally, the development of its special characteristics as well as its positive and/ or negative contribution (advantages and disadvantages) to the way the health services operate are examined. Organizational culture is characterized by difficulty in identifying its components in regards to every environment, it is facing resistance in change and needs time to be implemented.